From sacrifice to prestige: visualising the nation in 19th and 21st-century Serbia and Croatia. Issue 3 (3rd July 2017) - Malešević, Siniša
Abstract : This paper explores changing representations of the nation in 19th and 21st-century Serbia and Croatia. I analyse how the changed structural conditions influence different visualisation strategies of a nation over long periods of time. I show how the dominant 19th-century visual representations of nationhood in Croatia and Serbia were centred on violent images: representations of battlefields, personal sacrifices, large-scale forced migrations of the nation and the past military glories of medieval kingdom. In contrast, the 21st-century imageries tend to focus on the nation's international achievements in the fields of economy, science, technology, art and sports. On the surface, this significant visual shift would indicate that nationalism was a far more influential force in 19th Serbia and Croatia than is the case today. However, I argue that the opposite is the case: the changing representations of the nation in fact reflect a greater organisational and ideological penetration of nationalism in present-day Serbia and Croatia. While in the 19th century, violent images of the past largely served as a didactic tool for the socialisation of nationally ambiguous populations, in the 21st century, there is no need to perform such a role, as most citizens are already highly nationalised.